The Physiological and Cardiologic Effects of Long Video Gaming Sessions in Adult Males - Krarup, Kasper Bygum; Rantanen, Jesper Mosgaard; Mørk, Morten; Pedersen, Inge Søkilde; Christensen, Jeppe Hagstrup; Kristensen, Søren Risom; Handberg, Aase; Krarup, Henrik Bygum (Sports Medicine International Open, 2022)
The effect of long gaming sessions on energy intake, caffeine intake, blood pressure, heart rate, heart rate variability, and biochemical cardiac injury markers is unknown. The objective of this exploratory study was to investigate the changes in healthy male adults during two consecutive 18-hour sedentary video gaming sessions. Nine participants were enrolled in the study. Energy intake was noted in food diaries. Heart rate variability was monitored continuously; blood pressure and cardiac injury markers were measured every three to six hours. During the 42-hour study, the participants had an energy and caffeine intake of 8004.9 kcal and 1354.4 mg, respectively. The participants had a significant decrease in energy intake in the second session (p=0.01). A strong, negative correlation was found between body mass index and total energy intake (R=–0.84, p=0.005) and waist circumference and total energy intake (R=–0.70, p=0.036) in the first session. No nightly dip in blood pressure or heart rate was observed. Based on this study, long-term adverse effects of gaming cannot be ruled out. The non-dip of HR and BP suggests that long gaming sessions could be detrimental to cardiovascular health long term.
Keywords: sedentary video gaming; energy intake; caffeine intake; blood pressure; lifestyle; heart rate variability